Interplay Between Brain Dominance, Reading, and Speaking Skills in English Classrooms - Li, Shanshan; Hanafiah, Waode; Rezai, Afsheen; Kumar, Tribhuwan (Frontiers in Psychology, 2022)
Psychology and education are two inter-related fields. One of popular theories in psychology that potentially contributes to development of teaching and learning program is brain dominance. Brain is categorised into two hemispheres on the basis of personal traits and cognitive styles. The study discusses the correlation between brain dominance and two skills of English, Reading and Speaking. Data were randomly collected from 230 second semester students in four different universities and were analysed employing two statistic tests; Pearson Chi-Square test aimed at finding out correlation between the two variables, and Kruskal-Wallis test aimed at finding out the significant difference in the categories of brain dominance to Reading and Speaking scores, and Mann-Whitney test aimed at finding out the details of difference among groups of brain dominance. The test confirmed significant correlation between brain dominance and reading skill. Three categories of brain dominance groups differ in reading competence in which moderate right brain shows the highest score. In speaking skill, however, the test confirmed that there is no significant correlation between the brain dominance and speaking skill. Three groups of brain dominance are not significantly different in three aspects of speaking skill: accuracy, fluency and comprehensibility.